The relationship between promotion tools towards bumiputera awareness of Japanese Associate Degree under Yayasan Pelajaran MARA / Wan Rahimah Wan Ghazali - Wan Ghazali, Wan Rahimah (2012)
The main purpose of this study is to see the level of Bumiputera awareness towards Japanese Associate Degree program under Yayasan Pelajaran MARA. This research has been done in Kuala Lumpur area which is in Damansara area. The problem that face by the organization in determining the effectiveness or the suitable promotional tools that can help them increase Bumiputera awareness towards their program. The first objective of this study is to determine level of intention to know Japanese Associate Degree (JAD) program to Bumiputera. The second objective of this research is, to rank promotional mix element that can contribute intention to know this program. The next objective of this study is to determine the most effective promotional tools that can be used by the Yayasan Pelajaran MARA. The last objective of this study is to identify the solution or recommendation in improving promotional tools in creating Bumiputera awareness. For the research methodology, researcher used Exploratory and Simple Random Sampling in conducted this research study. The populations in this study were the people that come around the Damansara area. In this study researcher was decide to use Simple Random Sampling which is a Probability Sampling Technique that attempt to obtain a sample of random elements. The number of respondent for this research is 100 for this study, the researcher will use primary data and secondary data in order to collect data from the sample. The technique for collecting data is by using the questionnaire. As a result, there is no relationship or not significant between independent variable (advertising, personal selling, public relation and direct marketing) with the dependent variable (Bumiputera awareness). The organization (YPM) should take any appropriate strategies to encourage Bumiputera intention to known the existence Japanese Associate Degree (JAD) program.